2022
DOI: 10.1002/acr.24639
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences of Systemic Lupus Erythematosus: Findings From a Systematic Review, Meta‐Summary, and Meta‐Synthesis

Abstract: Objective: To explore the experience of patients with systemic lupus erythematosus (SLE).Methods: A systematic review of qualitative studies published in English in the past 10 years and identified through the PubMed, CINAHL, Scopus and Web of Science databases was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The methodological quality of each included study was assessed using the Critical Appraisal Screening Programme tool. Study findings were then sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
(233 reference statements)
0
9
0
Order By: Relevance
“…Interestingly, many patients in our study reported that overall energy levels, pain, sleep, and mood improved with dietary manipulation, suggesting that these quality of life (QoL) domains could benefit from nutritional interventions in rheumatic disease patients. This is especially important, as rheumatic disease patients, such as those with SLE, often have unmet QoL issues that do not correlate well with measured disease activity or use of immunosuppression (30,31). Indeed, prior studies of nutrition and/or dietary supplementation on patient-reported outcomes and QoL measures in rheumatic disease patients have found that nutritional intake favorably affects a variety of QoL domains, particularly in SLE and RA (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many patients in our study reported that overall energy levels, pain, sleep, and mood improved with dietary manipulation, suggesting that these quality of life (QoL) domains could benefit from nutritional interventions in rheumatic disease patients. This is especially important, as rheumatic disease patients, such as those with SLE, often have unmet QoL issues that do not correlate well with measured disease activity or use of immunosuppression (30,31). Indeed, prior studies of nutrition and/or dietary supplementation on patient-reported outcomes and QoL measures in rheumatic disease patients have found that nutritional intake favorably affects a variety of QoL domains, particularly in SLE and RA (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LE frequently experience detriments to quality of life and daily functioning [ 3 , 4 ]. Because of this, a number of qualitative studies were conducted over the last decade that attempted to better understand patient experiences with LE [ 5 ]. However, the large majority of these studies recruited participants from clinical settings; thus, clear gaps persist in understanding how experiences with LE can be improved in individuals outside the health care system [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 Fatigue and musculoskeletal pain are reported as the subjectively most burdensome symptom for patients with SLE. 7 Consequently, SLE has marked impact on morbidity, mortality, healthcare costs and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue occurs in >80%4 5 and is reported as the main barrier to maintaining employment in patients with SLE 6. Fatigue and musculoskeletal pain are reported as the subjectively most burdensome symptom for patients with SLE 7. Consequently, SLE has marked impact on morbidity, mortality, healthcare costs and quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation